The research of staffing trends in the financial sector through the prism of global changes - Луцик, Марія Василівна; Вознюк-Богів, Ірина Миколаївна (Technology audit and production reserves, 2016)
The current situation of the financial sector of Ukraine is characterized by a number of negative processes, namely the deepening crisis of confidence to the financial sector among the population, the growing share of problem assets on the balance sheets of banks, a significant outflow of deposits and others. This necessitated the approval of the Comprehensive Program of Ukraine’s financial sector by 2020. The National Bank of Ukraine sees the future of the financial sector in the light of reducing it: the number of commercial and state banks, the share of cash payments and the amount of cash in the money supply, the number of insurance companies etc. This led to the need to forecast the number of employed persons in the financial sector, which was done using the regression functions. The forecast results speak of downtrend. This situation is a logical continuation of global economic changes, such as digitalization, technological process, the emergence and development of financial technologies. This, in its turn, leads to changes in the employers’ requirements to their employees. It was revealed, that not the specific knowledge, but moral values of their personnel are the most important for the financial sector. This was also confirmed by the annual Report of the World Economic Forum. These results are important for the further training of specialists in the relevant areas.